Performance measurement in Agile development organizations - Korpivaara, Ida (2020)
Performance measurement plays a key role in enabling continuous improvement in Agile software development organizations. While previous studies and experience reports have suggested various metrics, little is known on the metrics and practices that Agile organizations use to measure their performance in practice. Particularly, there is a knowledge gap regarding the use of metrics on organizational level, even if Agile development methods are being increasingly adopted also by large organizations. This thesis aims to fill this gap by investigating what kind of performance objectives Agile development organizations have on different organizational levels and which metrics are used to measure them.